E-textiles: Power and resistance. Issue 1 (1st April 2020) - Wilkins, L. M.
On the precipice of space exploration, smart fabrics, biochips and exoskeletons, the materiality of our wearable and body-centric future is a critical and political issue. If we are to develop technologies to take us to new places, we should be able to imagine radically different futures. The materials, tools and supply chains available to us seed the future we can build and are fuel for the possibilities we can imagine. Textile-based Do It Yourself (DIY) electronics have been suggested in Maker technology circles as an alternative path to electronics to broaden the diversity of those imagining our future, but they are still heavily divided by lines of gender, and hindered by supply chain availability. There are many textile-based technologies that have unique technical qualities to offer, but their development is stifled by systemic issues. This article suggests that e-textile technologies are a result of an entrenched system of power and act as a control method over the vision of the future rather than the suggested notion that they are an avenue of exploration. Using Erbu Kurbak's concept of Lost Futures, and Elizabeth Ryan's interoperation of wearable technology as immaterial labour, I make the case for e-textile practice being a trap and never equal contributor to the technological discourse.